No evidence of increased cancer incidence in children using topical tacrolimus for atopic dermatitis - Paller, Amy S.; Fölster-Holst, Regina; Chen, Suephy C.; Diepgen, Thomas L.; Elmets, Craig; Margolis, David J.; Pollock, Brad H. (Journal of the American Academy of Dermatology, 2020)
Background - Long-term safety of topical calcineurin inhibitors is not well understood. APPLES (A Prospective Pediatric Longitudinal Evaluation to Assess the Long-Term Safety of Tacrolimus Ointment for the Treatment of Atopic Dermatitis; NCT00475605) examined incidence of lymphoma and other cancers in a pediatric population with atopic dermatitis. - Objective - To quantify incident malignancies during 10 years in children with atopic dermatitis who used topical tacrolimus for ≥6 weeks. - Methods - Standardized incidence ratios for cancer events were analyzed relative to sex-, age-, and race-matched control data from national cancer registries. - Results - There were 7954 eligible patients enrolled at 314 sites in 9 countries. During 44,629 person-years, 6 confirmed incident cancers occurred (standardized incidence ratio, 1.01; 95% confidence interval, 0.37-2.20). No lymphomas occurred. - Limitations - Observational prospective cohort study. - Conclusion - The cancer incidence was as expected, given matched background data. This finding provides no support for the hypothesis that topical tacrolimus increases long-term cancer risk in children with atopic dermatitis.
Gesehen am 30.10.2020